Noradrenaline transporter PET reflects neurotoxin-induced noradrenaline level decrease in the rat hippocampus - Takayuki Sakai; Saori Hattori; Aya Ogata; Takashi Yamada; Junichiro Abe; Hiroshi Ikenuma; Masanori Ichise; Masaaki Suzuki; Kengo Ito; Takashi Kato; Yasuyuki Kimura (EJNMMI Research, 2023)
Abstract Background The neuropathological changes of early Alzheimer’s disease (AD) include neurodegenerative loss of noradrenaline neurons in the locus coeruleus with decreasing noradrenaline availability in their projection areas such as the hippocampus. This diminishing noradrenaline availability is thought to play an important role pathophysiologically in the development of cognitive impairment in AD, because noradrenaline is not only essential for maintaining cognitive functions such as memory, learning and attention, but also its anti-inflammatory action, where its lack is known to accelerate the progression of AD in the mouse model. Therefore, the availability of in vivo biomarkers of the integrity of noradrenaline neurons may be beneficial for furthering our understanding of the role played by the noradrenaline system in the progressive cognitive dysfunction seen in AD patients. In this study, we investigated if PET imaging of noradrenaline transporters can predict the level of noradrenaline in the brain. Our hypothesis was PET measured noradrenaline transporter densities could predict the level of noradrenaline concentrations in the rat hippocampus after lesioning of noradrenaline neurons in this region. Results We chemically lesioned the hippocampus of rats (n = 15) by administering a neurotoxin, DSP-4, in order to selectively damage axonal terminals of noradrenergic neurons. These rats then underwent PET imaging of noradrenaline transporters using [11C]MRB ((S,S)-[11C]Methylreboxetine). To validate our hypothesis, postmortem studies of brain homogenates of these rats were performed to measure both noradrenaline transporter and noradrenaline concentrations. [11C]MRB PET showed decreased noradrenaline transporter densities in a DSP-4 dose-dependent manner in the hippocampus of these rats. In turn, these PET measured noradrenaline transporter densities correlated very well with in vitro measured noradrenaline concentrations as well as in vitro transporter densities. Conclusions [11C]MRB PET may be used as an in vivo biomarker of noradrenaline concentrations in the hippocampus of the neurodegenerating brain. Further studies appear warranted to extend its applicability to AD studies.